Critical Discourse Analysis of News Reporting on Human-Tiger Conflict in Riau Province - Rahman, Azizul; Agustin, Herlina; Mulyani, Henny Sri (Jurnal Kajian Jurnalisme, 2024)
Riau Province, as the habitat for almost one-third of the Sumatran tiger population, continues to grapple with the challenges of human-wildlife conflict. Mass media pays particular attention to cases of conflict involving protected animals, especially if such conflicts result in fatal casualties, as seen in the case of Tasik Tebing Serai Village. This research aims to critically analyze the media discourse construction related to this conflict, which can influence public awareness, community attitudes, and even policy responses. The critical discourse analysis method by Teun van Dijk is employed to identify text structures, social cognition, and social contexts in the news published by national and local media, namely detik.com and riaupos.co, reporting on the conflict in Tasik Tebing Serai Village, Riau Province. The research findings indicate that despite mass media presenting factual information, they need to catch up in providing education, a fundamental principle of environmental journalism. Detik.com leans towards utilizing the "rewrite" method to increase its publication quantity, whereas riaupos.co focuses more on presenting diverse topics. Both media have their own dramatic and sensational characteristics in delivering the news by utilizing the word of choice to catch the reader's attention to the issue. This study delves into a deeper understanding of the importance of reporting environmental issues with environmental journalism principles to enhance public awareness, understanding, and responsibility regarding environmental problems.